Factors Influencing Students’ Participation In Physical Activity And Sports In Senior High Schools In The Kassena Nankana Municipality, Ghana - Amoah, E.P. (University Of Ghana, 2021)
Sports and other types of physical activity have long maintained a thorny position in schools and colleges, frequently being relegated to the periphery. Simultaneously, there is agreement that such activities are vital for young people's healthy growth. This was proven in the second half of the twentieth century, resulting in a paradigm shift in health research. Recent advances in neurology, psychology, and allied fields point to a second revolution in which the tight separation of mind and body is no longer necessary. The main purpose of the study was to examine the factors influencing students’ participation in physical activity and sports in Senior High School in the Kassena Nankana Municipality of the Upper East Region of Ghana. Descriptive survey design was adopted for the study and quantitative methodology using a survey method was used to gather primary data from students and teachers. The research instruments used were the questionnaire and observation checklist. The self-administered data collection method was used in collecting information from respondents. The target population for the study involved all Senior High/Technical school students’ and P.E Teachers in the Kassena Nankana Municipality, Ghana. A total of 350 student respondents and 11 P.E Teachers were sampled for the study using the mathematical model expressed as: n=N / 1+N (e2) from the total population 5097 of students’ and all the P.E Teachers in the selected schools. Simple random sampling technique was used to select participants for the study and descriptive statistics (Frequency, percentages, mean and standard deviation) were used in analyzing and discussing the results. The study interestingly revealed that all students in the Senior High Schools were engaging in some form of physical activity and that is a good sign that students perceived the benefits of physical activity and sports to promote health and wellbeing. But on the contrary, the findings also showed that on the average, Senior High School students’ have a negative attitude (M=2.77, SD=1.42) towards participation in physical activity and sports and that has brought serious implications on their health and wellbeing. The factors that contribute to physical inactivity included; physical environment, biological or demographic, psychological, behavioural, social and cultural factors. The results showed that, societal misconception (67.14%), social role (55%), facilities and equipment (49.42%), requisite movement skills (49.14%), Motivation and self-confidence (49.14%) and on demographic and socio-economic factors, (49.14%) agreed that males participate more on physical activity than their female counterparts and ( 46.85%) also confirmed that young people also perform physical activity and sports than adults and these are significant factors influencing students’ non-participation in physical activity and sports in Senior High School in the Kassena Nankana Municipality, Ghana. It is recommended that after school games and activities should be made fun and the games should not be male dominated. Students should be educated on the importance of physical activity and sports.
MPhil. Education
Keywords: Kassena Nankana Municipality; Physical Activity; Sports; Senior High Schools